e-WOM Appeal and Brand Image: Shopee’s Strategy to Encourage Purchase Decision and Customer Satisfaction - Nazura, Azatul; Welsa, Henny; Setiawan, Budi (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The era of online buying and selling is increasingly growing and impacting the development of the e-commerce industry in Indonesia. This study was conducted to analyze the appeal of e-WOM and brand image in relation to Shopee's strategy to encourage purchasing decisions and customer satisfaction. This quantitative study selected 135 respondents as a criteria-based sample, namely consumers who have used the Shopee application. Data were analyzed using multiple linear regression methods, as well as partial and simultaneous hypothesis testing. Empirical findings indicate that e-WOM, brand image, and purchasing decisions have a positive and significant influence on consumer satisfaction. Furthermore, e-WOM and brand image have a positive and significant influence on purchasing decisions.